2019
DOI: 10.1016/j.ajodo.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of treatment recommendations based on digital vs plaster dental models

Abstract: The purpose of this study was to investigate differences in orthodontists' treatment plans based on digital models compared with plaster models. Additionally, we assessed whether digital or plaster models influence the reliability of orthodontists' treatment plans, as well as the amount of time required to arrive at the plan. Methods: Sixteen orthodontists planned treatment for 20 patients at 2 time points using either the same or different model formats (digital or plaster). The treatment plan decisions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Moreover, testing inexperienced operators in different impression methods could also enhance the scope of the study. For example, although Ko et al compared the time spent making the plans on the impression methods instead of impression‐taking time, they enhanced the scope of their study using different operators (16 orthodontist). The second limitation was that, in our study, a single intraoral scanner was used to take impressions and a single conventional impression was hand‐mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, testing inexperienced operators in different impression methods could also enhance the scope of the study. For example, although Ko et al compared the time spent making the plans on the impression methods instead of impression‐taking time, they enhanced the scope of their study using different operators (16 orthodontist). The second limitation was that, in our study, a single intraoral scanner was used to take impressions and a single conventional impression was hand‐mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Besides these controversial statements, Ko et al [15] and Yilmaz et al [12] showed in their studies that both models could be used without any negative implication for orthodontic treatments. These differences in measurements between different types of models can be linked to features such as malocclusions prior to treatment Verma et al [23], type of impression material [26] and type of printing technique [27,28], and that they may present statistically significant differences yet not clinically relevant to justify the contraindication of digital models [23,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This technology can generate digital study models by scanning the alginate impression or by direct intraoral scanning [2]. Much has been discussed about the accuracy and reproducibility of this technique, but studies report them as satisfactory so as not to interfere with the success of orthodontic planning, and the use of these models have become a reality in clinical practice [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of digital study models is that they are not prone to damage, fracture, or loss. Not only is no extra space needed to store the models, digital models also make setting up models and sending models for referral easy [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%